PENENTUAN AWAL BULAN ISLAM MENURUT MAZHAB SYAFI’I - Musyafaâ€™, Muhammad Alwi (UIN ALAUDDIN MAKASSAR, 2020)
The problem of determining the beginning of the qomariyah month in Indonesia is always up for discussion. The problem of determining the beginning of the qomariyah month has not yet found a common point. This problem stems from differences in the understanding of the traditions about the beginning of the month which are still general. There are several people whose understand textually, namely the rukyat camp, and there are several others who understand contextually, namely the hisab camp. Apart from understanding the two camps, we must also understand how the opinions of previous scholars, especially the opinions of the four schools of scholars, are often used as references in their opinion. In this case, the four scholars have different opinions regarding the method of determining the beginning of the qomariyah month, some of they are using rukyat, and some of they are using hisab. In this discussion, the author will examine the method of determine the beginning of the qomariyah month from the perspective of Syafi’i schools. Among the though of the Syafi’i schools there are two opinions, namely using the rukyat method and the hisab method. However, the hisab method takes precedence or priority over the rukyat method, it means that if there is a rukyah al-hilal that is successfully carried out, while in hisab there is no possibility that the hilal can be seen, the hisab decision takes precedence and rukyat is rejected.Keywords : Determining the beginning of the qomariyah month, Hisab, Rukyat.